ANALYSIS OF TENSILE STRENGTH AND MACRO STRUCTURE OF 6061 ALUMINUM ALLOY RESULTING FROM GMAW AND GTAW WELDING - Salahudin, Xander; Waluyo, Edi; Hastuti, Sri (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Aluminium 6061 material is often used in the shipbuilding industry, especially as a construction frame on ships. GMAW (Gas Metal Arc Welding) and GTAW (Gas Tungsten Arc Welding) are widely used in welding aluminium alloy materials. This research aims to determine and analyse the effect of V, X, and U groove variations welded using GMAW and GTAW on tensile strength of a 6061 aluminium alloy. The results of this study obtained the highest tensile stress value from the X groove GMAW welding of 149.22 MPa with a strain of 8.60%. The lowest tensile stress value was obtained from the U groove GTAW welding of 105.09 MPa with a strain of 3.18%. In general, the tensile strength value of GMAW welding is better than GTAW welding. Macro photo observations of GMAW welding show a small amount of porosity welding defects at the base of the weld, while GTAW welding shows a more amount of porosity welding defects at the base of the weld.